2021
DOI: 10.1111/febs.16182
|View full text |Cite
|
Sign up to set email alerts
|

Protease‐sensitive regions in amyloid light chains: what a common pattern of fragmentation across organs suggests about aggregation

Abstract: Light-chain (AL) amyloidosis is characterized by deposition of immunoglobulin light chains (LC) as fibrils in target organs. Alongside the full-length protein, abundant LC fragments are always present in AL deposits. Herein, by combining gel-based and mass spectrometry analyses, we identified and compared the fragmentation sites of amyloid LCs from multiple organs of an AL k amyloidosis patient (AL-55). The positions pinpointed here in kidney and subcutaneous fat, alongside those previously detected in heart o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 42 publications
5
29
0
Order By: Relevance
“…Accordingly, few biochemical studies showed that the full-length LCs could be involved in the initial nucleation thanks to its stability which serves as a platform for the subsequent elongation by unstable VLs ( 34 36 ). These experimental results are in line with the observations made by mass spectrometry both in diagnosis using laser microdissection/mass spectrometry (LMD/MS) ( 37 ) and in more careful analyses of deposited protein contents ( 38 ) showing that a complete or partially degraded C domain is always present in the amyloid deposits ( 39 ), and the degradation patterns argue for a post-deposition proteolysis. Whether C domain proteolysis occurs before or after aggregation and contributes or conversely protects from amyloidogenesis in vivo is still under debate ( 3 , 39 ), but using the sole VL to study amyloidogenesis of LCs in vitro is likely a reduced approach that do not mirror the in vivo process.…”
Section: To V or Not To V?supporting
confidence: 87%
“…Accordingly, few biochemical studies showed that the full-length LCs could be involved in the initial nucleation thanks to its stability which serves as a platform for the subsequent elongation by unstable VLs ( 34 36 ). These experimental results are in line with the observations made by mass spectrometry both in diagnosis using laser microdissection/mass spectrometry (LMD/MS) ( 37 ) and in more careful analyses of deposited protein contents ( 38 ) showing that a complete or partially degraded C domain is always present in the amyloid deposits ( 39 ), and the degradation patterns argue for a post-deposition proteolysis. Whether C domain proteolysis occurs before or after aggregation and contributes or conversely protects from amyloidogenesis in vivo is still under debate ( 3 , 39 ), but using the sole VL to study amyloidogenesis of LCs in vitro is likely a reduced approach that do not mirror the in vivo process.…”
Section: To V or Not To V?supporting
confidence: 87%
“…8). In addition, two segments, [12][13][14][15][16][17][18][19][20][21][22] (which was not certified by peer review) is the author/funder. All rights reserved.…”
Section: Hdx Ms Studies Of Al2 Gl2 Al2cdr3 and Gl2cdr3 Lcsmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted February 3, 2023. ; https://doi.org/10.1101/2023.02.01.526662 doi: bioRxiv preprint can follow the misfolding rather than precede it [4,18], and the exact sequence of steps leading to formation of AL deposits remains to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…High resolution mapping of peptide termini by mass spectrometry recently revealed a more complex picture, consistent with multiple proteolytic events after amyloid fibril formation [ 73 , 74 ]. Proteolytic events after fibril formation are also suggested by the recent cryo-electron microscopy-delineated structures of TTR amyloid fibrils in the hearts of late-onset familial amyloidosis patients [ 75 ].…”
Section: Al Amyloid Is Assembled From Non-natively Folded Lc Peptidesmentioning
confidence: 99%